Ethical values for excellence in education and science - Kapur, Jagat Narain, 1923- (New Delhi : Wishwa Prakashan, 1996)
Collection of lectures and addresses delivered by the author on different occasions with reference to Indian society.
Includes bibliographical references.
Keywords: Moral education -- India; Values -- Study and teaching -- India; Education -- Aims and objectives -- India; Science -- Study and teaching -- Moral and ethical aspects -- India; 95-90 ; 03